Systematic revision and molecular phylogeny of the land snail genus Fruticocampylaea (Gastropoda: Hygromiidae) from the Caucasus region. Issue 1 (2nd January 2016) - Walther, Frank; Neiber, Marco T.; Hausdorf, Bernhard
Abstract : This paper presents a systematic revision and a molecular phylogenetic analysis of the Caucasian land snail genus Fruticocampylaea . The genus is newly delimited based on the reduction of the cavities adjoining the seminal duct in the penial papilla. Shell and genitalia of all five species ( F. narzanensis, F. kobensis, F. tushetica sp. nov., F. christophori, F. daghestana ) are described and figures provided. All synonyms and all locality records are listed. Maximum likelihood and Bayesian analyses of mitochondrial and nuclear DNA sequences (fragments of cox1, 16S rDNA, ITS2 and 28S rDNA) confirm the monophyly of Fruticocampylaea . The reduction of the dart apparatus and the conical plug, via which the dart apparatus inserts into the vagina, as well as the molecular phylogenetic analyses, suggests a sister group relationship between Fruticocampylaea and Circassina (without Abchasohela ). Furthermore, the molecular phylogenetic analyses indicate that the Fruticocampylaea species originated in a rapid radiation. The uplift of the Greater Caucasus in the Late Miocene or Pliocene or climatic changes at the end of the Pliocene or in the early Pleistocene may have caused the radiation of Fruticocampylaea . Low intraspecific variability can be explained by population bottlenecks during Pleistocene glacial periods followed by postglacial population increase. http://zoobank.org/urn:lsid:zoobank.org:pub:AB15158D-21A3-4945-8D49-F7DE8E406E2B